Enzyme replacement therapy for mucopolysaccharidosis VI: long‐term cardiac effects of galsulfase (Naglazyme®) therapy. Issue 2 (5th June 2012) - Braunlin, E.; Rosenfeld, H.; Kampmann, C.; Johnson, J.; Beck, M.; Giugliani, R.; Guffon, N.; Ketteridge, D.; Sá Miranda, C. M.; Scarpa, M.; Schwartz, I. V.; Leão Teles, E.; et al.
Abstract: Characteristic cardiac valve abnormalities and left ventricular hypertrophy are present in untreated patients with mucopolysaccharidosis type VI (MPS VI). Cardiac ultrasound was performed to investigate these findings in subjects during long‐term enzyme replacement therapy (ERT) with recombinant human arylsulfatase B (rhASB, rhN‐acetylgalactosamine 4‐sulfatase, galsulfase, Naglazyme®). Studies were conducted in 54 subjects before ERT was begun and at specific intervals for up to 96 weeks of weekly infusions of rhASB at 1 mg/kg during phase 1/2, phase 2, and phase 3 trials of rhASB. At baseline, mitral and aortic valve obstruction was present and was significantly greater in those ≥12 years of age. Mild mitral and trace aortic regurgitation were present, the former being significantly greater in those <12 years. Left ventricular hypertrophy, with averaged z‐scores ranging from 1.6–1.9 SD greater than normal, was present for ages both <12 and ≥12 years. After 96 weeks of ERT, ventricular septal hypertrophy regressed in those <12 years. For those ≥12 years, septal hypertrophy was unchanged, and aortic regurgitation increased statistically but not physiologically. Obstructive gradients across mitral and aortic valves remained unchanged. The results suggest that long‐term ERT is effective in reducing intraventricular septal hypertrophy and preventing progression of cardiac valve abnormalities when administered to those <12 years of age.